ChemInform Abstract: Catalytic C—H α‐Trifluoromethylation of α, β‐Unsaturated Carbonyl Compounds. Issue 34 (26th August 2014) - Fang, Zhongxue; Ning, Yongquan; Mi, Pengbing; Liao, Peiqiu; Bi, Xihe
Abstract Application of this method is demonstrated by the trifluoromethylation of several bioactive drugs.